(untitled) (Pedagogy of Higher and Secondary Education, 2009)
"Problem of adaptation of the credit-module system of evaluation to the special course "Technology of picturesque materials" on the artistic-graphic faculties of pedagogical university" is examined question about the method of evaluation ofprogress of students in obedience to technology of implementation of concrete practical exercises.